IPO underpricing in the Chinese A-share market: Winner’s curse and ex ante uncertainty - Zhang, Wenlu (2017)
A large number of researches shows that Initial Public Offerings (IPOs) of common stocks are systematically priced at a discount to their initial trading price. The large underpricing magnitude in the Chinese IPO market has drawn much attention. In this paper, A-share initial public offerings (IPOs) were 36.6458% underpriced from 2010 to 2016.